2020
DOI: 10.1080/13880209.2020.1761404
|View full text |Cite
|
Sign up to set email alerts
|

The synergistic antitumour effect of multi-components from Pulsatilla chinensis saponins in NCI-H460 lung cancer cell line through induction of apoptosis

Abstract: Context: Pulsatilla chinensis (Bunge) Regel (Ranunculaceae) possess antitumour effects; however, its antitumour potential has not been extensively investigated. Objective: To investigate the synergetic effect of multi-components from P. chinensis induced cell apoptosis and explore the mechanism. Materials and methods: The cytotoxicity was measured against NCI-H460, SMMC-7721, HCT-116 and U251 cell lines treated with eight monomers from P. chinensis. The synergetic effect of a combination of Pulsatilla saponin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…Apoptosis is accompanied by changes in cell morphology, such as cell volume reduction, nuclear membrane shrinkage, chromatin concentration and aggregation, and apoptotic bodies (Zhang et al 2015). HA1 has a signi cant inhibitory effect on many types of tumor cell lines (NCI-H460, ZR75-1, HL-60, SMMC-7721, Bel-7402, MCF-7) by inducing apoptosis (Gerkens et al 2007;Liang et al 2016;Wang et al 2018;Guan et al 2020). HA1 can reportedly induce the apoptosis of breast cancer cells (ZR75-1 and MCF-7) and increase the expression of cleaved PARP and caspase-3 (Liang et al 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Apoptosis is accompanied by changes in cell morphology, such as cell volume reduction, nuclear membrane shrinkage, chromatin concentration and aggregation, and apoptotic bodies (Zhang et al 2015). HA1 has a signi cant inhibitory effect on many types of tumor cell lines (NCI-H460, ZR75-1, HL-60, SMMC-7721, Bel-7402, MCF-7) by inducing apoptosis (Gerkens et al 2007;Liang et al 2016;Wang et al 2018;Guan et al 2020). HA1 can reportedly induce the apoptosis of breast cancer cells (ZR75-1 and MCF-7) and increase the expression of cleaved PARP and caspase-3 (Liang et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The molecular mechanisms of the antitumor effects of HA1 remain uncertain, except for its reported membrane damage and high a nity for melanin (Delmas et al 2000;Debiton et al 2004). To date, research on the molecular mechanism is mainly limited to the inhibition of the PI3K/AKT/mTOR signaling pathway (Wang et al 2018;Guan et al 2020;Zhang et al 2020). It has been shown that STAT3 is crucial in numerous tumorigenesis processes, and activation of the JAK-STAT pathway plays a crucial role in the antiproliferation and apoptosis induction of breast cancer cells (Sansone et al 2012;Ma et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study, we demonstrated that three monomers of Pulsatilla chinensis , PSA, R13, and PSD, can considerably inhibit the proliferation of tumour cell lines (Guan et al. 2020 ). α-Hederin ( Figure 1(a) ) is a monosaccharide chain pentacyclic triterpenoid saponin and is one of the effective components of the traditional Chinese medicine Pulsatilla chinensis .…”
Section: Introductionmentioning
confidence: 99%
“…Pulsatilla chinensis (Bunge) Regel (Ranunculaceae), which is used for its cooling and detoxifying abilities, has been reported to have many pharmacological characteristics such as being antimalarial and antibacterial (Cheng et al 2008) and an anticancer agent (Liu et al 2013). In our previous study, we demonstrated that three monomers of Pulsatilla chinensis, PSA, R13, and PSD, can considerably inhibit the proliferation of tumour cell lines (Guan et al 2020). a-Hederin (Figure 1(a)) is a monosaccharide chain pentacyclic triterpenoid saponin and is one of the effective components of the traditional Chinese medicine Pulsatilla chinensis.…”
Section: Introductionmentioning
confidence: 99%